Preparation method of CoNC catalyst for preparing ethylene glycol through ethylene oxidation
The synthesis of CoNC catalysts by high-temperature calcination method solves the problems of low selectivity of ethylene oxidation and high economic cost, and achieves efficient oxidation under normal temperature and pressure, reducing by-product generation and energy consumption.
Patent Information
- Application Number
- CN202411585283.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-28
AI Technical Summary
The selectivity of ethylene oxidation to ethylene glycol is low, the economic cost is high, and the operating conditions of traditional thermal catalytic methods are harsh, with many by-products, making it difficult to separate.
The CoNC catalyst was synthesized by high-temperature calcination method. By controlling the addition amount and calcining temperature of the precursor, the coverage and binding energy of *OH were adjusted to achieve efficient oxidation of ethylene to ethylene glycol.
The yield of ethylene oxidation into ethylene glycol is improved, the generation of by-products is reduced, and high selective oxidation is achieved under normal temperature and pressure, reducing energy consumption and environmental pollution.
Smart Images

Figure CN119530854A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of ethylene oxidation, and designs a method for preparing a CoNC catalyst for ethylene oxidation to ethylene glycol. Background Art
[0002] Ethylene glycol (EG), also known as salicylic acid and ethylene glycol ether, is an important organic chemical raw material with a wide range of industrial uses. Ethylene glycol is the simplest diol. Since 1953, the industrial production of ethylene glycol has been widely used. Due to its excellent water solubility, it is widely used in food, beverage and feed industries. As the simplest aliphatic diol, it is an important intermediate in chemical processes. It is mainly used as a solvent, antifreeze and lubricant. It is also an important raw material for the preparation of alcohols, ethers, esters, phenols, etc. It also makes great contributions to papermaking, synthetic resins and food industries. Its terminal application areas are closely related to basic needs such as clothing, food, housing and transportation. Ethylene glycol is mainly used in the manufacture of polyester, so its industry belongs to a part of the polyester industry chain. Ethylene glycol mainly belongs to the upstream petrochemical industry in the polyester industry chain.
[0003] The traditional thermal catalytic ethylene oxidation reaction is carried out under high temperature and pressure, and the reaction will release a lot of heat, which requires the consumption of fossil energy to control the system temperature and avoid thermal runaway. The operating conditions are relatively harsh. At the same time, during the reaction, excessive oxidation of ethylene will generate aldehydes, ketones, CO 2 Therefore, in order to reduce the use of fossil energy and improve the selectivity of ethylene oxidation, a highly selective electrochemical ethylene oxidation method can be sought to electrochemically oxidize ethylene into target products at room temperature and pressure, improve product selectivity, and reduce carbon dioxide emissions during ethylene oxidation.
[0004] Generally, electrochemical oxidation of ethylene can be divided into two categories: direct electrochemical oxidation and indirect electrochemical oxidation. In the direct electrochemical oxidation reaction route, which is carried out on the electrode surface, a transition metal catalytic system is used. The generation of reaction intermediates requires a high overpotential, and the use of catalysts reduces the kinetic barriers of the reaction. The indirect electrochemical ethylene oxidation route, on the other hand, is to achieve the oxidation of ethylene by introducing a redox medium, accelerate the electron transfer rate between ethylene molecules and electrodes, reduce the overpotential of the ethylene reaction, and improve the selectivity of the product.
[0005] The one-step oxidation of ethylene to ethylene glycol under electrocatalytic conditions has obvious advantages, and according to previous studies, it has been found that Pd-based materials have good catalytic effects on the adsorption of ethylene and the production of ethylene glycol. However, Pd is a precious metal with a relatively high price, which makes the cost of the catalyst an important economic consideration in large-scale industrial applications. Compared with Pd, Co is a relatively abundant and inexpensive metal. In large-scale industrial production, the use of Co materials as catalysts can significantly reduce production costs and improve the economy of the production process. The use of Co materials can reduce dependence on precious metals and reduce resource consumption and environmental pollution in the production process. At the same time, Co catalysts may have better green chemical properties during the reaction process, which meets the requirements of modern industry for environmentally friendly production processes. We mainly synthesized CoNC catalysts by high-temperature calcination to increase the *OH coverage and adjust the binding energy of *OH, so that ethylene can be smoothly oxidized to ethylene glycol. Summary of the invention
[0006] The purpose of the present invention is to solve the problem of low selectivity and high economic cost of ethylene oxidation to ethylene glycol, develop a CoNC catalyst with high catalytic efficiency, and provide a preparation method of the catalyst. The method adopts a high-temperature calcination method to synthesize the optimal CoNC catalyst by controlling the amount of precursor added and the calcination temperature.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing a CoNC catalyst for ethylene oxidation to ethylene glycol comprises the following steps:
[0009] Step 1. Add a certain proportion of cobalt nitrate hexahydrate and zinc nitrate hexahydrate into 50 ml of methanol, which is referred to as solution A.
[0010] Step 2. Dissolve 6.5 g of dimethylimidazole in 50 ml of methanol, referred to as solution B.
[0011] Step 3. Mix solution A and solution B in step 1 and step 2 together and stir overnight for 24 hours.
[0012] Step 4. After the mixture in step 3 is stirred, add 50-100 ml of methanol to wash and filter to obtain a solid powder, and dry it in a vacuum oven at 80°C for 12 hours.
[0013] Step 5. The solid powder obtained in step 4 was vacuum dried and then ground, and calcined at 1000° C. for 3 hours under an argon atmosphere to obtain a CoNC catalyst.
[0014] Step 6. Grind the solid catalyst obtained in step 5 and take 5 mg, add 20 μl of nafion and 980 μl of isopropanol to make a slurry, and ultrasonicate for 30 minutes.
[0015] Step 7. After ultrasonication, take 10 μl of the slurry prepared in step 6 and apply it on a 1*1.5 cm 2 on carbon paper and used as anode material for electrocatalytic reactions.
[0016] The present invention has the following advantages:
[0017] 1. This method synthesizes CoNC material catalysts. Co-based materials are more environmentally friendly in chemical reactions and have low economic costs. Ethylene gas is introduced through a conduit and reacts on the catalyst surface, which can save the intermediate step of ethylene oxide formation and directly synthesize ethylene glycol in one step, also saving the cost of downstream product separation.
[0018] 2. This method uses an H-type cell, into which ethylene is introduced to separate the positive and negative electrodes, so that the pH on the catalyst surface is continuously acidic and is not affected by the cathode hydroxide ions;
[0019] 3. The maximum yield of ethylene to ethylene glycol over CoNC catalyst in this method is 6.32 μmol / cm 2 / h (reaction time one hour), the amount of other by-products is very small, which provides a way for the directional oxidation of ethylene. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is the XRD pattern of CoNC catalyst;
[0021] Figure 2 The yield of ethylene oxidation to ethylene glycol over CoNC catalyst (three different cobalt-zinc ratios) in ethylene atmosphere for 1 hour;
[0022] Figure 3 The partial current density diagram of the ethylene oxidation to ethylene glycol reaction of CoNC catalyst (three different cobalt-zinc ratios) in ethylene atmosphere for 1 hour;
[0023] Figure 4 The concentration of CoNC catalyst (3 different cobalt-zinc ratios) in 16 ml electrolyte was measured after ethylene oxidation to ethylene glycol in ethylene atmosphere for 1 hour. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below with reference to the accompanying drawings and embodiments.
[0025] Example 1
[0026] First, 3g of cobalt nitrate hexahydrate and 1.5g of zinc nitrate hexahydrate were added to 50ml of methanol, which was recorded as liquid A. In addition, 6.5g of dimethylimidazole was added to 50ml of methanol, which was recorded as liquid B. Then liquid B was slowly poured into liquid A. After the addition of white dimethylimidazole, the solution changed from a red solution to a purple suspension. At this time, the solution was placed on a magnetic stirrer, the beaker opening was sealed with a sealing film, and stirred at an appropriate stirring rate for 24 hours. After stirring, the solution was placed in a suction filtration bottle, and organic filter paper was used for suction filtration. During the suction filtration process, the beaker was cleaned with methanol, and then the solid obtained by suction filtration was placed in a petri dish, wrapped with tin foil to prevent contamination, and placed in an oven, with the temperature set to 80°C and the time set to 720 minutes. After drying, the sample was placed in a tubular furnace, and calcined for 3 hours at a temperature of 1000°C and a heating rate of 2°C / min under an argon atmosphere. After calcination, the black solid in the tubular furnace was taken out and ground to obtain CoNC catalyst A. The above materials were subjected to XRD test, and the results were as follows Figure 1 As shown in A, the Co signal is not obvious. Take 5 mg and place it in a 5 ml centrifuge tube, add 20 μl nafion and 980 μl isopropanol, mix well and ultrasonicate for 30 minutes to prepare CoNC catalyst A slurry. Apply the ultrasonicated slurry dropwise on a 1*1.5 cm 2 On the carbon paper, the drop coating area is 1*1cm 2 , use a baking lamp to dry it and set it aside. The carbon paper that was dripped with CoNC catalyst after drying was used for ethylene oxidation experimental test: a three-electrode system was used. In an H-type electrolytic cell, the carbon paper dripped with catalyst material was used as the working electrode, Ag / AgCl was used as the reference electrode, and the platinum sheet was used as the counter electrode. The voltage was 2.6V (RHE) for 1 hour. During the reaction, ethylene gas was introduced into the anode at a gas rate of 25ml / min, and a magnetic stirrer was added to make the gas diffuse evenly in the solution. After the reaction, 870μl of the anode reaction liquid was taken for nuclear magnetic resonance detection and product analysis. Figure 2 As shown in A, the yield is 3.82 μmol / cm 2 / h, such as Figure 3 As shown in A, the bias current density is 0.2 mA / cm 2 ,like Figure 4 As shown in A, the concentration of ethylene glycol in 16 ml of electrolyte is 14.82 ppm.
[0027] Example 2
[0028] First, add 4.5g of cobalt nitrate hexahydrate and 1.5g of zinc nitrate hexahydrate to 50ml of methanol, which is recorded as liquid A; in addition, add 6.5g of dimethylimidazole to 50ml of methanol, which is recorded as liquid B; then slowly pour liquid B into liquid A. After the addition of white dimethylimidazole, the solution changes from a red solution to a purple suspension. At this time, place the solution on a magnetic stirrer, seal the beaker opening with a sealing film, and stir at an appropriate stirring rate for 24 hours. After stirring, place the solution in a suction filtration bottle, use organic filter paper for suction filtration, and wash the beaker with methanol during the suction filtration process. Then place the solid obtained by suction filtration in a petri dish, wrap it with tin foil to prevent contamination, and place it in an oven with a temperature set to 80°C and a time of 720 minutes. After drying, the sample was placed in a tube furnace and calcined for 3 hours at a temperature of 1000°C and a heating rate of 2°C / min under an argon atmosphere. After the calcination, the black solid in the tube furnace was taken out and ground to obtain CoNC catalyst B. The above materials were subjected to XRD testing, and the results were as follows: Figure 1 As shown in B, there is an obvious Co signal. Take 5 mg and place it in a 5 ml centrifuge tube, add 20 μl nafion and 980 μl isopropanol, mix well and ultrasonicate for 30 minutes to prepare CoNC catalyst B slurry. Apply the ultrasonicated slurry dropwise on a 1*1.5 cm 2 On the carbon paper, the drop coating area is 1*1cm 2 , use a baking lamp to dry it and set it aside. The carbon paper that was dripped with CoNC catalyst after drying was used for ethylene oxidation experimental test: a three-electrode system was used. In an H-type electrolytic cell, the carbon paper dripped with catalyst material was used as the working electrode, Ag / AgCl was used as the reference electrode, and the platinum sheet was used as the counter electrode. The voltage was 2.6V (RHE) for 1 hour. During the reaction, ethylene gas was introduced into the anode at a gas rate of 25ml / min, and a magnetic stirrer was added to make the gas diffuse evenly in the solution. After the reaction, 870μl of the anode reaction liquid was taken for nuclear magnetic resonance detection and product analysis. Figure 2 As shown in B, the yield is 6.32 μmol / cm 2 / h, such as Figure 3 As shown in B, the partial current density is 0.34mA / cm 2 ,like Figure 4 As shown in B, the concentration of ethylene glycol in 16 ml of electrolyte is 24.54 ppm.
[0029] Example 3
[0030] First, add 6.5g of cobalt nitrate hexahydrate and 1.5g of zinc nitrate hexahydrate to 50ml of methanol, which is recorded as liquid A; in addition, add 6.5g of dimethylimidazole to 50ml of methanol, which is recorded as liquid B; then slowly pour liquid B into liquid A. After the addition of white dimethylimidazole, the solution changes from a red solution to a purple suspension. At this time, place the solution on a magnetic stirrer, seal the beaker opening with a sealing film, and stir at an appropriate stirring rate for 24 hours. After stirring, place the solution in a suction filtration bottle, use organic filter paper for suction filtration, and wash the beaker with methanol during the suction filtration process. Then place the solid obtained by suction filtration in a petri dish, wrap it with tin foil to prevent contamination, and place it in an oven with a set temperature of 80°C and a time of 720 minutes. After drying, the sample was placed in a tube furnace and calcined for 3 hours at a temperature of 1000°C and a heating rate of 2°C / min under an argon atmosphere. After the calcination, the black solid in the tube furnace was taken out and ground to obtain CoNC catalyst C. The above materials were subjected to XRD testing, and the results were as follows: Figure 1 As shown in C, there is an obvious Co signal, but it is not as sharp as B. Take 5 mg and place it in a 5 ml centrifuge tube, add 20 μl Nafion and 980 μl isopropanol, mix well and ultrasonicate for 30 minutes to prepare CoNC catalyst C slurry. Spread the ultrasonicated slurry dropwise on a 1*1.5 cm 2 On the carbon paper, the drop coating area is 1*1cm 2 , and bake it dry with a baking lamp for later use. The carbon paper coated with CoNC catalyst after drying was used for ethylene oxidation experimental test: a three-electrode system was used, in an H-type electrolytic cell, the carbon paper coated with catalyst material was used as the working electrode, Ag / AgCl was used as the reference electrode, and the platinum sheet was used as the counter electrode. The voltage was 2.6V (RHE) for 1 hour. During the reaction, ethylene gas was introduced into the anode at a gas rate of 25ml / min, and a magnetic stirrer was added to allow the gas to diffuse evenly in the solution. After the reaction, 870μl of the anode reaction liquid was taken for nuclear magnetic resonance detection and product analysis. Figure 2 As shown in C, the yield is 2.44 μmol / cm 2 / h, such as Figure 3 As shown in C, the partial current density is 0.13mA / cm 2 ,like Figure 4 As shown in C, the concentration of ethylene glycol in 16 ml of electrolyte is 9.46 ppm.
[0031] Example 4
[0032] First, 4.5g of cobalt nitrate hexahydrate and 1g of zinc nitrate hexahydrate were added to 50ml of methanol, which was recorded as liquid A. In addition, 6.5g of dimethylimidazole was added to 50ml of methanol, which was recorded as liquid B. Then liquid B was slowly poured into liquid A. After the addition of white dimethylimidazole, the solution changed from a red solution to a purple suspension. At this time, the solution was placed on a magnetic stirrer, the beaker opening was sealed with a sealing film, and stirred at an appropriate stirring rate for 24 hours. After stirring, the solution was placed in a suction filtration bottle, and organic filter paper was used for suction filtration. During the suction filtration process, the beaker was cleaned with methanol, and then the solid obtained by suction filtration was placed in a petri dish, wrapped with tin foil to prevent contamination, and placed in an oven, the temperature was set to 80°C, and the time was 720 minutes. After drying, the sample was placed in a tubular furnace, and calcined for 3 hours at a temperature of 1000°C and a heating rate of 2°C / min under an argon atmosphere; after calcination, the black solid in the tubular furnace was taken out and ground to obtain CoNC catalyst D. The above materials were subjected to XRD test, and the results were as follows Figure 1 As shown in D, there is also an obvious Co signal. Take 5 mg and place it in a 5 ml centrifuge tube, add 20 μl nafion and 980 μl isopropanol, mix well and ultrasonicate for 30 minutes to prepare CoNC catalyst D slurry. Apply the ultrasonicated slurry dropwise on a 1*1.5 cm 2 On the carbon paper, the drop coating area is 1*1cm 2 , use a baking lamp to dry it and set it aside. The carbon paper that was dripped with CoNC catalyst after drying was used for ethylene oxidation experimental test: a three-electrode system was used. In an H-type electrolytic cell, the carbon paper dripped with catalyst material was used as the working electrode, Ag / AgCl was used as the reference electrode, and the platinum sheet was used as the counter electrode. The voltage was 2.6V (RHE) for 1 hour. During the reaction, ethylene gas was introduced into the anode at a gas rate of 25ml / min, and a magnetic stirrer was added to make the gas diffuse evenly in the solution. After the reaction, 870μl of the anode reaction liquid was taken for nuclear magnetic resonance detection and product analysis. Figure 2 As shown in D, the yield is 2.76 μmol / cm 2 / h, such as Figure 3 D shows that the partial current density is 0.15 mA / cm 2 ,like Figure 4 As shown in D, the concentration of ethylene glycol in 16 ml of electrolyte is 10.73 ppm.
[0033] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a CoNC catalyst for ethylene oxidation to ethylene glycol, characterized in that: The following steps are involved: Step 1. Add 3-6.5 g of cobalt nitrate hexahydrate and 1-1.5 g of zinc nitrate hexahydrate into 50 ml of methanol, which is referred to as solution A. Step 2. Dissolve 6.5 g of dimethylimidazole in 50 ml of methanol, referred to as solution B; Step 3. Mix the A and B solutions in step 1 and step 2 together and stir on a magnetic stirrer; Step 4. After the mixture in step 3 is stirred, add 50-100 ml of methanol for washing, filter to obtain a solid powder, and dry it in a vacuum oven; Step 5. The solid powder obtained in step 4 is vacuum dried and then ground, and calcined at 1000° C. for 3 hours under an argon atmosphere to obtain a CoNC catalyst; Step 6. Grind the solid catalyst obtained in step 5, take 5 mg, add 20 μl of nafion and 980 μl of isopropanol to make a slurry; Step 7. After ultrasonic treatment, take out the slurry prepared in step 6 and apply it dropwise on a 1*1.5cm 2 on carbon paper and used as anode material for electrocatalytic reactions.
2. The method for preparing a CoNC catalyst for ethylene oxidation to ethylene glycol according to claim 1, characterized in that: In step 3, the stirring time is 24 hours.
3. The method for preparing a CoNC catalyst for ethylene oxidation to ethylene glycol according to claim 1, characterized in that: In step 4, vacuum drying is performed at 80° C. for 12 hours.
4. The method for preparing a CoNC catalyst for ethylene oxidation to ethylene glycol according to claim 1, characterized in that: In step 5, the calcination heating rate is 2°C / min.
5. The method for preparing a CoNC catalyst for ethylene oxidation to ethylene glycol according to claim 1, characterized in that: In step 6, the resulting slurry was sonicated for 30 minutes.
6. The method for preparing a CoNC catalyst for ethylene oxidation to ethylene glycol according to claim 1, characterized in that: In step 7, 10 μl of the slurry material is evenly dropped onto the carbon paper.
Citation Information
Cited By
Preparation method of Ru-WO3 nano-catalyst as well as product and application of Ru-WO3 nano-catalyst
CN120797035A